2020
DOI: 10.3390/cancers12082130
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Biology of Osteosarcoma

Abstract: Osteosarcoma (OS) is the most frequent primary bone cancer in children and adolescents and the third most frequent in adults. Many inherited germline mutations are responsible for syndromes that predispose to osteosarcomas including Li Fraumeni syndrome, retinoblastoma syndrome, Werner syndrome, Bloom syndrome or Diamond–Blackfan anemia. TP53 is the most frequently altered gene in osteosarcoma. Among other genes mutated in more than 10% of OS cases, c-Myc plays a role in OS development and promotes cell invasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
214
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(219 citation statements)
references
References 186 publications
(253 reference statements)
1
214
0
4
Order By: Relevance
“…In the present study, miR-766-3p was lowly expressed in OS tissue specimens and cells, negatively related with OS malignancy, and might be used as a novel treating target for OS. Emerging research has demonstrated that the abnormal miRNA expression plays key regulatory role in OS progression (Czarnecka et al, 2020;Zhang H. et al, 2020), the potential mechanism of miR-766-3p has not been investigated. miR-766-3p has recently been recognized as a tumor suppressor through the β-catenin pathway in several tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, miR-766-3p was lowly expressed in OS tissue specimens and cells, negatively related with OS malignancy, and might be used as a novel treating target for OS. Emerging research has demonstrated that the abnormal miRNA expression plays key regulatory role in OS progression (Czarnecka et al, 2020;Zhang H. et al, 2020), the potential mechanism of miR-766-3p has not been investigated. miR-766-3p has recently been recognized as a tumor suppressor through the β-catenin pathway in several tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Axitinib stabilized refractory osteosarcoma in two children [ 188 ], whereas pazopanib, despite good preclinical results [ 123 ], did not prevent progression [ 213 , 214 , 215 ]. Among MKIs, sorafenib stabilized the disease [ 213 , 216 ], maintaining a prolonged partial response during 51 months in a child with refractory osteosarcoma [ 217 ].…”
Section: Antiangiogenics and Bone Sarcomasmentioning
confidence: 99%
“…One of the best clinical responses obtained with antiangiogenics in osteosarcomas was using cabozantinib. The CABONE study, which included children and adults, showed that 37% of patients had a PFS at least 33% longer than when using other conventional therapies [ 215 ]. The only study published on imatinib showed no response, although it should be noted that the dose was lower than in other studies [ 141 , 167 ].…”
Section: Antiangiogenics and Bone Sarcomasmentioning
confidence: 99%
“…1 The 5-year survival rate of OS has been greatly improved to approximately 60-70% due to the use of neoadjuvant chemotherapy in combination with surgery. 2 However, the long-term survival rate of patients has not been further improved in recent decades due to local relapse or early lung metastasis even after curative excision of the primary tumor and intensive chemotherapy. 3 Thus, novel pharmacological molecules or strategies for OS and the further elucidation of the underlying molecular mechanism are urgently needed to improve patient survival.…”
Section: Introductionmentioning
confidence: 99%